2018
DOI: 10.7759/cureus.2853
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Phlegmasia Cerulea Dolens Secondary to Heparin-induced Thrombocytopenia Leading to Gangrene

Abstract: We present a case of a dialysis-dependent end-stage renal disease patient who originally presented with sepsis and later developed heparin-induced thrombocytopenia-related upper extremity deep venous thrombosis that rapidly progressed to phlegmasia. Argatroban, a direct thrombin inhibitor, was initiated without delay. Argatroban restored the venous patency completely but did not reverse his two gangrenous fingers. The patient finally underwent digital amputation. The management of this uncommon, but life-threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, majority PCD cases involved lower extremity, while upper extremity PCD is extremely rare and account for less than 5% of all PCD cases (4,5). Malignancy, hypercoagulable state, infection, venous stasis, heart diseases and central venous catheter implantation had been identified as common risk factors of DVT and PCD in previous studies, moreover, heparin-induced thrombocytopenia and pacemaker were also reported to induce PCD and venous gangrene (3,(7)(8)(9)(10)(11). The association between venous thromboembolism (VTE) and malignancy has been well studied and described before.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, majority PCD cases involved lower extremity, while upper extremity PCD is extremely rare and account for less than 5% of all PCD cases (4,5). Malignancy, hypercoagulable state, infection, venous stasis, heart diseases and central venous catheter implantation had been identified as common risk factors of DVT and PCD in previous studies, moreover, heparin-induced thrombocytopenia and pacemaker were also reported to induce PCD and venous gangrene (3,(7)(8)(9)(10)(11). The association between venous thromboembolism (VTE) and malignancy has been well studied and described before.…”
Section: Discussionmentioning
confidence: 98%
“…Weaver et al [ 7 ] describe three therapeutic measures for the management of PCD: IV heparin, venous thrombectomy, and thrombolytic therapy, and more recently oral anticoagulants like argatroban have been described to be effective under special circumstances by other authors [ 8 ]. Their data suggest that non-gangrenous forms of PCD have a successful response to systemic anticoagulation.…”
Section: Discussionmentioning
confidence: 99%